In situ characterization of the Ca2+ sensitivity of large conductance Ca2+-activated K+ channels: implications for their use as near-membrane Ca2+ indicators in smooth muscle cells. - Muñoz, A (1998)
The Ca2+ sensitivity of large conductance Ca2+- and voltage-activated K+ channels (BKV,Ca) has been determined in situ in freshly isolated myocytes from the guinea pig urinary bladder. In this study, in situ denotes that BKV,Ca channel activity was recorded without removing the channels from the cell. By combining patch clamp recording in the cell-attached configuration and microfluorometry of fura-2, we were able to correlate BKV,Ca channel activity with changes in cytoplasmic intracellular [Ca2+] ([Ca2+]i). The latter were induced by ionomycin, an electroneutral Ca2+ ionophore. At 0 mV, the Hill coefficient (nH) and the [Ca2+]i to attain half of the maximal BKV,Ca channel activity (Ca50) were 8 and 1 microM, respectively. The data suggest that this large Hill number was not a consequence of the difference between the near-membrane [Ca2+] ([Ca2+]s) and the bulk [Ca2+]i, indicated by fura-2. High Hill numbers in the activation by Ca2+ of BKV,Ca channels have been seen by different groups (e.g., filled squares in Fig. 4 of Silberberg, S. D., A. Lagrutta, J. P. Adelman, and K. L. Magleby. 1996. Biophys. J. 70:2640-2651). However, such high nH has always been considered a peculiarity rather than the rule. This work shows that a high Ca2+ cooperativity is the normal situation for BKV,Ca channels in myocytes from guinea pig urinary bladder. Furthermore, the Ca50 did not display any significant variation among different channels or cells. It was also evident that BKV,Ca channel activity could decrease in elevated [Ca2+]i, either partially or completely. This work implies that the complete activation of BKV,Ca channels occurs with a smaller increment in [Ca2+]s than previously expected from in vitro characterization of the Ca2+ sensitivity of these channels. Additionally, it appears that the activity of BKV,Ca channels in situ does not strictly follow changes in near-membrane [Ca2+].